Uso do espaço por Gracilinanus agilis (Didelphimorphia) e Wiedomys pyrrhorhinus (Rodentia) em área de caatinga no alto sertão sergipano - Cruz, Arthur Oliveira da (2016)
Studies on communities of small mammals (rodents and marsupials) show different patterns on both selection and use of space in relation to diet, age, and seasonality, among others. To evaluate these standards, spool-and-line technique can provide information about the movement, vertical stratification and the use of shelters and nests by animals. The aim of this study was to evaluate the usage area and selection of microhabitat by Gracilinanus agilis (Didelphimorphia) and Wiedomys pyrrhorhinus (Rodentia) in Monumento Natural Grota do Angico (MNGA), between the cities of Canindé de São Francisco and Poço Redondo, both in Sergipe state. The study was conducted by using Sherman traps to capture the animals, and spool-and-line technique to characterize the movement of these animals in two areas of shrub caatinga vegetation of MNGA, between December/2014 and September/2015. For each individual, data were obtained on the daily home range (AUD), tortuosity of the movement (TORT), index of vertical use (VU) and ground use (%SOLO). The sample for microhabitat selection and availability was performed with ground and canopy cover data and vertical foliar obstruction only to dry period. We evaluated 44 routes (27 G. agilis and 17 W. pyrrhorhinus) representing 2451.42 m of traced line. No differences were found in the movement variables between the dry and rainy seasons for both species (p> 0.0919). Males and females of G. agilis and W. pyrrhorhinus also did not show difference for these variables (p> 0.0643). Comparing the two species, the only difference was on the vertical use (p = 0.0050). Only W. pyrrhorhinus females showed microhabitat selection during daily movement (p <0.0001). Regarding the daily home range (AUD), G. agilis presented, in general, a larger area than W. pyrrhorhinus. Low values of tortuosity (TORT) could be associated with the low population density of these species in the area. The difference in the vertical use (VU) was expected since G. agilis is reported as a scansorial species while W. pyrrhorhinus is preferably arboreal. In general, the absence of habitat selection by sampled environmental variables suggests that G. agilis and W. pyrrhorhinus may be performing this selection on the mesohabitat scale.